El ocio como mecanismo politico de control: tras la búsqueda mítica del triunfo - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Science, 2008)
Somehow, the different politic regimes have been linked to great public event organization and deport achievements. At this work, we intend to demonstrate as some isolated variable as charisma, etno-genesis, hegemony and archetype go together and explain the liaison between Political Power and Leisure.
Keywords: Politics structures; Leisure; Events of sport Competition